Original paperPulsed dose rate brachytherapy of lip cancer - Serkies, Krystyna; Ziemlewski, Adam; Sawicki, Tomasz; Kamińska, Joanna; Dziadziuszko, Rafał (Journal of Contemporary Brachytherapy, 2013)
Purpose: To present our experience with pulsed dose rate brachytherapy (PDR BT) of lip cancer. Material and methods: The study group included 32 T1-4N0M0 lip cancer patients with a median age of 71 years (ranged 41-87 years), treated with interstitial PDR BT to the planned total dose of 60-70 Gy; 1 Gy/pulse, pulses repeated every hour a day. There were 26 untreated patients, and six patients after previous surgery including five implanted at the time of cancer relapse. Results : PDR BT was delivered over few days and was well tolerated. After therapy, all patients experienced temporary, usually mild, acute mucositis. Late severe (Grade 3) mucositis of oral vestibule mucosa occurred in one case. Among 31 patients who completed the therapy, local control was achieved in 29 (93.5%). One patient with reccurrent upper lip T2 tumor was susccessfully salvaged surgically, another one died due to persisted T3 lip tumor with lymph node metastases. Overall, four patients developed neck nodal cancer relapse and two – distant metastases. The 5-year local control, and all-cause overall survival probabilities are 94% and 73%, respectively. Good/excellent cosmetic and functional outcome was obtained in all but two patients. Conclusions : PDR at the dose of 1 Gy/pulse is effective and well tolerated BT technique in treating lip cancer patients.